The Taking of Land: When Should Compensation be Paid? - Blume, Lawrence; Rubinfeld, Daniel L.; Shapiro, Perry (Quarterly Journal of Economics, 1984)
The analysis focuses on the question of whether the payment of compensation for land taken by eminent domain is efficient. When the taking decision is independent of land use, zero compensation is efficient, but full compensation is not. When the project decision is no longer independent of land use, and can be affected by investor decisions, neither compensation rule is generally efficient because of the moral hazard problem. With risk-averse consumers and risk-neutral firms, the previous conclusions remain essentially unchanged. However, when the project decision rule involves a budgetary “fiscal illusion,” additional compensation may be necessary to correct the incentives facing the project decision-maker.